ANALISIS JEJARING AKTOR DALAM PENGEMBANGAN DESA CERDAS BERBASIS PENTAHELIX STUDI KASUS DESA KERTAYASA KABUPATEN KUNINGAN JEJARING - Mulyono, Dicky Rizkialdy; Widmarija, Arsal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The challenge in eradicating poverty in rural areas requires innovative development approaches supported by the roles of actors within the pentahelix dimension. The pentahelix dimension consists of actors including the government, businesses, academia, communities, and the media, who support the development of a smart village in Kertayasa Village. This study analyzes the network of actors within the pentahelix dimension in relation to the development of a smart village, which brings about transformative impacts through the roles of interconnected actors. The research adopts a qualitative study approach, focusing on Kertayasa Village in Sindangagung Sub-district, Kuningan Regency, West Java Province. The analysis employs the social network analysis framework, which utilizes graph theory to measure the interconnectedness of actors and identify the involvement of interconnected actors within the pentahelix dimension. The adoption of the smart village concept applied in Kertayasa Village, analyzed through the use of social network analysis theory, demonstrates support among actors within the pentahelix dimension, leading to transformative impacts on indicators within the smart village encompassing smart governance, smart economy, smart mobility, smart environment, smart people, and smart living.Keywords: Actor network, smart village, pentahelix, social network analysis